La riprogettazione post sisma: verso nuove reti di engagement all-of-society - D’Ambrosi, Lucia; Polci, Valentina; Sargolini, Massimo (SocietàMutamentoPolitica, 2023)
The article presents the results of a study aimed at investigating the engagement networks activated in the planning process of the territories affected by the 2016 earthquake in the Marche region. The research objective is to reflect on communication strategies implemented by a selection of municipal administrations to promote transparency and information sharing and, at the same time, citizen participation in design and planning processes. The results highlight the emergence of an all-of-society engagement approach, to experiment and co-create with a renewed relationship between institutions, science, and local communities.